Identification and Screening of Bioactive Phytocompounds against Matrix Metalloproteinase-9, Targeting Cancer Cell Proliferation and Angiogenesis: Phytocompounds Targeting MMP-9 in Cancer - Haque, Faiqua; Showkat, Bisma; Rasheed, Khalid; Ansari, Imran; Pawar, Varsha; Alam, Mudassir; Shadab, G.G.H.A. (Iranian Journal of Pharmaceutical Sciences, 2025)
Matrix metalloproteinase-9 (MMP-9) is a zinc-dependent endopeptidase that plays a key role in tumor progression, metastasis, and angiogenesis by degrading extracellular matrix components and modulating cell signaling pathways. Due to its overexpression in various cancers and contribution to tumor microenvironment remodeling, MMP-9 is a critical therapeutic target for cancer therapy. This study employed a comprehensive computational strategy to identify natural MMP-9 inhibitors from phytochemical databases. Different bioinformatics methods, such as molecular docking, ADME/T profiling, PASS analysis, pIC50 analysis, drug-likeness prediction, and molecular dynamic (MD) simulation, were carried out. Molecular docking analysis revealed strong binding affinities for Naringenin (-9.5 kcal/mol) and Rhamnetin (-8.9 kcal/mol), which formed stable interactions with MMP-9's catalytic domain. PASS analysis further validated their inhibitory potential (Naringenin: Pa = 0.764; Rhamnetin: Pa = 0.755). Crucially, both compounds exhibited exceptional ADME/T properties, such as high oral bioavailability, optimal metabolic stability, and low toxicity risks, which are essential for preclinical drug development. The molecular dynamics simulations confirmed their binding stability, with favorable hydrogen bonding patterns and minimal structural fluctuations. Other promising candidates like Epigallocatechin-gallate, Naringenin, and Rhamnetin emerged as beautiful leads due to their dual advantages of potent MMP-9 inhibition and drug-like pharmacokinetic profiles. The findings support advancing these phytochemicals into experimental studies as potential anti-cancer agents targeting MMP-9-mediated pathological processes in cancer development.